Book review: Broto, V. C. and Westman, L. 2019: Urban Sustainability and Justice: Just Sustainabilities and Environmental Planning. (January 2022) - Tihani, Salma
Broto, V. C. and Westman, L. 2019: Urban Sustainability and Justice: Just Sustainabilities and Environmental Planning . London: Zed Books Ltd. 208 pp., £65 (Hardback). ISBN: 978-1-78699-492-9.